Дослідження монументальної споруди XIV—XV ст. у м. Володимир-Волинський у 2009 р. - Златогорський, О.Є.; Лукомський, Ю.В.; Панишко, С.Д. (Археологічні дослідження в Україні, 2010)
A 14th—15th c. monumental building identified and partly studied by the Expedition of the State Enterprise «Volyn Antiquities » at 19a, Drahomanova Street in Volodymyr-Volynskyi is briefly described.